China`s climate change policies - Wang, Weiguang 1950-; Zheng, Guoguang; Pan, Jiahua (London Routledge, 2012)
"This report, prepared by the Chinese Academy of Social Sciences, brings together leading analysts in the scientific assessment of climate change, relevant social and economic policy and those who directly participate in international climate negotiations. The report provides a comprehensive understanding of the latest developments in the global response to climate change since the Copenhagen and Cancun climate conferences and Chinese actions in response, the results of these actions, the challenges that are still being faced, as well as China's long-term strategy in response to climate change. Part one focuses on the Chinese domestic policy response to climate change, including an analysis of the fulfilment of the energy conservation targets in the 11th Five Year Plan, pathways and policies to meet the 40%-45% target by 2020, China's adaptation strategy and policies, low carbon buildings, carbon sinks of forestry, public participation, and the low carbon city idea that the Shanghai World Expo has promoted. Part two includes thematic studies on some interesting hot topics, such as carbon tariff, indicators for assessment of low carbon cities, methodology for assessment of adaptation to climate change and cumulative carbon emissions. Finally, the annex includes key data on population, the economy, energy consumption and emissions by sector, as well as progress to meet 11th Five Year Plan energy conservation targets in each Chinese region. "--
"At the end of 2010 in the coast city, Cancun, Mexico, the United Nations Framework Convention on Climate Change (UNFCCC) convened its 16th Conference of the Parties (COP16), which received another round of great attention from the whole world. This book calls together experienced experts with in-depth understanding on scientific assessment of climate change and relevant social and economic policies and senior experts who directly participate in the international climate negotiations. This will help the readers to better understand the upcoming Durban conference, as well as China's long-term strategy in response to climate change. This book includes researches on China's 12th Five year plan; pilot low carbon city actions; policies and pathways for China's national appropriate mitigation actions; China's forestry management; China's NGOs and climate change; low carbon expo in Shanghai China 2010; Carbon budget proposal; China's green economy and green jobs; China's reaction to carbon tariff; China's actions in adaptation approaches; China's accumulative carbon emissions, etc. This gives the readers a comprehensive understanding of the latest developments of China's actions in response to climate change, the results of these actions, and the challenges that are still being faced. China is becoming a raising star in global economical and political affairs. Both international society and China itself have great expectation to its future role. This book clarifies China's leading position in many aspects. However, limited to its development stage, natural resource endowment, and other unbalanced developing issues, China is still a developing country. This book reveals a real China to the audience, which can provide a more comprehensive solution to future global climate regime"--
Includes bibliographical references and index.
Keywords: Carbon dioxide mitigation -- Economic aspects -- China; Carbon dioxide mitigation -- Government policy -- China; Climatic changes -- Government policy -- China; Climatic changes -- Social aspects -- China; Political Science / Public Policy / Environmental Policy